Investigating the electromagnetic wave-absorbing capacity and mechanical properties of flexible radar-absorbing knitted compound materials. (September 2021) - Chen, Niuniu; Wei, Sainan; Shi, Bao; Yan, Ruosi; Li, Xianghong; Zhan, Tianhang
This study fabricated flexible radar-absorbing knitted compound materials by weft knitting and blending ferromagnetic nickel micron-fibers and cotton fiber into structures with a concave–convex surface, including rhombic, mat, wavy, and leno stitches. The electromagnetic wave-absorbing capability and mechanical properties of the flexible radar-absorbing knitted compound materials were evaluated. The results showed that the rhombic, mat, and wavy stitches displayed high mechanical properties with high bursting strength and there were no significant differences among them. The rhombic stitch flexible radar-absorbing knitted compound material with a ferromagnetic nickel micron-fiber content of 14% had a maximum bandwidth of 13 GHz and achieved a minimum reflectance of −20 dB at 7 GHz, which was 150% that of mat fabric, and 200% that of wavy fabric and leno fabric. This was ascribed to the fact that the concave–convex surface with regular diamond-shaped block improved the dispersion of the electromagnetic wave, weakened the wave strength, and increased the interference. Therefore, the rhombic stitch flexible radar-absorbing knitted compound material was the most suitable for flexible radar-absorbing material in this study. The development of flexible radar-absorbing materials, by combining aerospace technology, military technology and textile technology, is important for the application in stealth of aircraft and weapons.